Implementation Of Modification Game Methods To Improve Breaststroke Swimming Skills - Ruslan Abdul Gani; Hasanuddin Jumareng; Kuswahyudi Kuswahyudi; Oman Unju Subandi; Edi Setiawan (Universitas PGRI Palembang, 2021)
The breaststroke is a swimming style that is loved by everyone because it is so easy to do. The purpose of this study was to improve breaststroke swimming skills in the 2018/2019 physical education study program students through the application of the modified game method. The method used in this research is a classroom action research methodology research design by Kemmis and Mc.Taggart. he subjects in this study were 31 students of the PJKR study program who took the aquatic learning course II, the results of this study were from the initial test data that 8 students were in the complete category or about 26%, there was an increase in the first cycle, 20 students were included in the category. complete or about 65%, and in cycle II, there was a very large increase with 29 students in the complete category or around 94%, this research was in accordance with the set target, namely 90%. he conclusion of this study is that the application of the modified game method is effective in improving breaststroke swimming skills in physical education study program students class of 2018/2019